2007
DOI: 10.1002/met.6
|View full text |Cite
|
Sign up to set email alerts
|

Weather and cycling—a first approach to the effects of weather conditions on cycling

Abstract: ABSTRACT:In urban and suburban recreation areas, walking and cycling constitute an important part of leisure activities. Both activities involving motion, are not only carried out for recreation but also for commuting to and from work. The mixture of recreation and commuting cycling is a challenge for park management. Conflicts between user groups, such as walkers and cyclists, exist due to the different movement speeds and also different user profiles: walkers, leisure cyclists and cyclists who commute have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 10 publications
3
57
0
5
Order By: Relevance
“…Thus, this study observes weather conditions and their relation to bathing and sunbathing. Of course, the relationship between human behaviour and atmospheric and climatic conditions is intuitively obvious and has been widely recognised for many years (Brandenburg et al 2007). In this regard, the analysis of an in situ phenomenon can be considered the most appropriate path for undertaking a study of tourism climatology, especially if the activity is largely determined by weather conditions, as is the case with the use and enjoyment of beaches.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this study observes weather conditions and their relation to bathing and sunbathing. Of course, the relationship between human behaviour and atmospheric and climatic conditions is intuitively obvious and has been widely recognised for many years (Brandenburg et al 2007). In this regard, the analysis of an in situ phenomenon can be considered the most appropriate path for undertaking a study of tourism climatology, especially if the activity is largely determined by weather conditions, as is the case with the use and enjoyment of beaches.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have addressed the sensitivity of weather conditions on bicycle activity (Brandenberg et al 2007; Nankervis 1999a; Nankervis 1999b; Thomas et al 2009;Winters et al 2007;Richardson 2000;Richardson 2006). Counts taken in April for instance, during the same hour and the same day of the week can be very different depending on weather conditions such as temperature, humidity, and precipitation.…”
Section: B Weather Correction Methodsmentioning
confidence: 99%
“…Most common among these are rain and temperature, which are present in almost all of the studies. Most studies found that cycling decreases in the presence of rain or with an increase in rainfall (Key 1992, Emmerson et al 1998, Nankervis 1999, Richardson 2000, Cervero and Duncan 2003, Dill and Carr 2003, Pucher and Buehler 2006, Brandenburg et al 2007, Winters et al 2007, Parkin et al 2008, Phung and Rose 2007, Ahmed et al 2010, Heinen et al 2011, Smith and Kauermann 2011, Miranda-Moreno and Nosal 2011, Ahmed et al 2012, Buehler and Pucher 2012, Flynn et al 2012, Tin et al 2012, Thomas et al 2013. Only a few studies found that rain had no statistically significant effect on cycling, and most of those (e.g.…”
Section: Review Of Literaturementioning
confidence: 99%